Dopant/carrier profiling for 3D‐structures. Issue 1 (9th December 2013) - Vandervorst, Wilfried; Schulze, Andreas; Kambham, Ajay Kumar; Mody, Jay; Gilbert, Matthieu; Eyben, Pierre; Cristiano, Fuccio; Pichler, Peter; Tavernier, Clément; Windl, Wolfgang
Abstract With the transition from planar to three‐dimensional device architectures such as FinFets, TFETs and nanowires, new metrology approaches are required to characterize the 3D‐dopant and carrier distributions precisely, as their positioning relative to gate edges, 3D‐distribution, conformality, and absolute concentration determine the device performance in great detail. Concepts like atomprobe tomography with its inherent 3D‐resolution are obviously a potential solution although its routine application is still hampered by localization problems, reconstruction artifacts due to inhomogeneous evaporation, sensitivity due to the limited statistics, poor tip yield, etc. Although on the other hand concepts like scanning spreading resistance microscopy are inherently 2D, extensions towards 3D appear possible either by the design of dedicated tests structures or by novel approaches such as mechanical scalping. Ultimately even 1D‐methods like secondary ion mass spectrometry can be used to study dopant incorporation in 3D‐structures. When assessing their performance as metrology tool for 3D‐devices and structures one needs to address not only their ability to achieve 3D‐spatial resolution but also the physical property which is probed, i.e. dopants versus carriers, as well as the complexity of the method used. An evaluation in terms of time to data is equally important as the technical capabilities. The application of these methods to 3D‐structures and confined volumes, has demonstrated that the changing surface/volume ratios in confined devices versus blanket films lead to phenomena (dopant deactivation, enhanced diffusion, ..) which cannot be observed in blanket experiments. Hence more emphasis should be placed on the analysis of device and structures with the relevant dimensions relative to the exploration of blanket experiments. (© 2014 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)